Dampak Kemiskinan Terhadap Kesejahteraan Masyarakat Kotanopan Secara Ekonomi Islam - Hardana, Ali; Siregar, Sulaiman Efendi; Hasibuan, Lismawati; Utami, Try Wahyu (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2024)
This research is descriptive qualitative field research. This field research was conducted in Kotanopan Village, Mandailing Natal Regency, North Sumatra Province. This research used the side quota method consisting of 15 quotas taken from 3 RTs in Hamlet 001, as well as interviews with the village head. Next, this research problem was analyzed using a qualitative data analysis method that uses a deductive thinking approach. The research results show that several causes of poverty in Kotanopan Village are as follows: low level of education; lack of funds; and family responsibilities. Based on these factors, poverty has the impact of losing people's welfare rights such as clothing, food and shelter, because some people still live in semi-permanent homes, losing the right to education because parents cannot teach their children, and losing the right to get a decent job because the head of the family does not have enough education so they cannot pay their children's school fees.